2021
DOI: 10.1093/gerona/glab305
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Features and Risk Factors for Mortality Among Long-term Care Facility Residents Hospitalized Due to COVID-19 in Spain

Abstract: Background COVID-19 severely impacted older adults and long-term care facility (LTCF) residents. Our primary aim was to describe differences in clinical and epidemiological variables, in-hospital management, and outcomes between LTCF residents and community-dwelling older adults hospitalized with COVID-19. The secondary aim was to identify risk factors for mortality due to COVID-19 in hospitalized LTCF residents. Methods This… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
1
3
0
Order By: Relevance
“…On the other hand, we observed a lower in-hospital mortality rate in older patients with COVID-19 who acquired the infection in long-term care facilities compared with patients with community-acquired disease. This finding has previously been described and explained by the possible earlier identification and treatment of COVID-19 symptoms as well as earlier hospitalization of these patients [ 57 ].…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…On the other hand, we observed a lower in-hospital mortality rate in older patients with COVID-19 who acquired the infection in long-term care facilities compared with patients with community-acquired disease. This finding has previously been described and explained by the possible earlier identification and treatment of COVID-19 symptoms as well as earlier hospitalization of these patients [ 57 ].…”
Section: Discussionsupporting
confidence: 73%
“…In support of the latter argument, we found that patients admitted after the first wave showed fewer clinical and laboratory criteria of severity and had a shorter duration of symptoms than patients hospitalized in the first wave. Fourth, we do not have data on the SARS-CoV-2 strains of patients hospitalized with COVID-19 and cannot rule out that the reduction in complications and mortality observed after the first wave may be at least partially explained by a lower virulence of SARS-CoV-2 in successive waves [ 57 ]. Finally, this study is limited to unvaccinated patients.…”
Section: Discussionmentioning
confidence: 99%
“…It is unclear whether the good outcomes observed in elderly patients treated with remdesivir could be due to immunosenescence in this population [25]. If so, the earlier use of antiviral therapy in these patients could be another explanation of the better response to antivirals, in light of the fact that they accessed medical care earlier [26], when the efficacy of treatment is higher.…”
Section: Discussionmentioning
confidence: 98%
“…Dyspnea has also been associated with mortality in many reports [ 22 , 23 ]. Other important factors independently associated with COVID-19 mortality in the literature included advanced age, increased C-reactive protein, reduced renal function, coronary artery disease, increased frailty [ 16 ], and poor preadmission functional status [ 24 , 25 , 26 ]. Mortality was 1.3 times greater in immunosuppressed patients with nosocomial compared to community-acquired infection [ 17 ].…”
Section: Discussionmentioning
confidence: 99%